2002
DOI: 10.1177/152660280200900512
|View full text |Cite
|
Sign up to set email alerts
|

Early Ambulation after Diagnostic Angiography Using 4-F Catheters and Sheaths: A Feasibility Study

Abstract: It is feasible and safe to ambulate patients 3 hours after diagnostic angiography performed with a 4-F catheter with or without a 4-F sheath. Early ambulation of patients after angiography has the additional benefits of increasing patient satisfaction and resource utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 6 publications
0
25
0
1
Order By: Relevance
“…There were also studies which used a combination of manual compression with a mechanical compression clamp, 18,19,22,37 compression clamp devices only, 31,34 sandbags or gauze pressure dressings only 11,32 . Two trials did not mention the methods of haemostasis used 17,33 . None of the trials indicated that they used any form of vascular closure devices.…”
Section: Discussionmentioning
confidence: 99%
“…There were also studies which used a combination of manual compression with a mechanical compression clamp, 18,19,22,37 compression clamp devices only, 31,34 sandbags or gauze pressure dressings only 11,32 . Two trials did not mention the methods of haemostasis used 17,33 . None of the trials indicated that they used any form of vascular closure devices.…”
Section: Discussionmentioning
confidence: 99%
“…Published recumbent times range from 1 to 6 hours after use of 4-F catheters (3,20). The necessary time to remain in a flat position after an arterial procedure varies from institution to institution and is a confounding factor in determining the significance of early ambulation after percutaneous closure.…”
Section: Patient Ambulation and Comfortmentioning
confidence: 99%
“…There is some evidence that patients undergoing hepatic artery chemoembolization as well as UAE are in hypercoagulable states for as long as 24 hours after the procedure (31,32). Four-F catheters are de rigeur for diagnostic studies in many interventional and cardiology catheterization laboratories (3,20,(37)(38)(39). Do these agents predispose patients to thrombotic events after percutaneous closure?…”
Section: What Questions Are Unanswered?mentioning
confidence: 99%
See 2 more Smart Citations